Simulation Study on the Transmission Characteristics of Downhole Wireless Radio Frequency Identification Signal - WANG Anni; WU Jiafeng; WANG Shujun; HAO Zaisheng; DU Xiaocan; LI Guangze (Cejing jishu)
Wireless radio frequency identification (RFID) technology can be used to remotely control downhole tools. It is the new development direction of intelligent drilling and well completion technology because of the advantages of non-contact transmission, low power consumption, convenient operation, low cost, etc. However, the complex downhole environment can have a great impact on the reliability of downhole wireless RFID signal transmission. In this paper, the transmission model for the downhole wireless RFID signal is established by combining the Maxwell’s equations and Faraday’s law of electromagnetic induction. Different transmission media and other downhole environmental impacts are comprehensively considered. And the accuracy of the theoretical model is verified by numerical simulations. Based on this model, the influences of excitation voltage amplitude, transmission distance and drilling fluid properties on downhole radio frequency signal transmission characteristics are analyzed. The research results show that: with the increasing of the drilling fluid conductivity, the signal attenuation increases; with the increasing of the transmission distance, the transmission strength of the radio frequency signal becomes weaker; with the increasing of excitation voltage amplitude, the transmission strength of radio frequency is stronger; the minimum deviation between the transmission model and the simulation model can reach 1.67%, which has certain reference value. This research can provide theoretical basis for wireless transmission technology of downhole tools and help promote the development of wireless transmission technology of downhole information.